A special judo fitness test classificatory table - Franchini, E.; Vecchio, F. B.; Sterkowicz, S. (Archives of Budo, 2009)
Background and study aim: Judo is very physiological demanding sport, but there are no many physical fitness specific tests. One of the most used specific judo tests is the Special Judo Fitness Test (SJFT) proposed by Sterkowicz (1995). Although this test has been used by many coaches in different countries no classificatory table was found to classify the judo athletes according to their results. Thus, the aim of this work was to present a classificatory table for this test. Material and methods: For this purpose 141 judo athletes (mean ±standard deviation: 21.3±4.5 years-old; 74.2±15.9 kg of body mass and 176.7±8.2 cm of height; judo ranking between 3rd kyu and 3rd dan) familiarized with the SJFT performed it once in order to provide data to establish a classificatory table. Results: After the analysis of data distribution a five scale table (20% for each classificatory category) was developed considering the variables used in the SJFT (number of throws, heart rate after and 1 min after the test and index). Conclusions: The classificatory table can help coaches using the SJFT to classify their athletes` level and to monitor their physical fitness progress. Testvideot: http://www.archbudo.com/text.php?ids=252